Description of Management Mental Disorders - Dian Utama Pratiwi Putri; Mona Jesica Efendi; Kodrat Pramudho; Endang Budiati (Global Health Science Group, 2021)
People with mental disorders are the official designation for mental disorders based on mental health law number 18 of 2014. Mental disorders have not fully attained good behavior and fulfilled human rights needs, the government provides protection and guarantees mental health services for people. with mental disorders based on human rights. The research objective is known to in-depth analyze the management people with mental disorders in the community in 2020. This type of research is qualitative and the results of the research are presented in a descriptive way. Subjects or informants were taken by purposive sampling. Informants in this study were as many is 7 people. Data collection techniques using in-depth interviews and observations. Based conducted in-depth interviews with 7 informants, there are 3 factors that influence the management of , namely (objective, subjective, iatrogenic burden). And it is known that the institutions involved in the implementation of the protection of the rights of health services are (Health Service, Social Service, Hospitals and Puskesmas). The rights of health services can be fulfilled maximally by the existence of cooperation between related institutions that complement each other.